In vitro blood flow in a rectangular PDMS microchannel: experimental observations using a confocal micro-PIV system - Lima, Rui A. (2008)
Progress in microfabricated technologies has attracted the attention of researchers in several areas, including microcirculation. Microfluidic devices are expected to provide powerful tools not only to better understand the biophysical behavior of blood flow in microvessels, but also for disease diagnosis. Such microfluidic devices for biomedical applications must be compatible with state-of-the-art flow measuring techniques, such as confocal microparticle image velocimetry (PIV). This confocal system has the ability to not only quantify flow patterns inside microchannels with high spatial and temporal resolution, but can also be used to obtain velocity measurements for several optically sectioned images along the depth of the microchannel. In this study, we investigated the ability to obtain velocity measurements using physiological saline (PS) and in vitro blood in a rectangular polydimethysiloxane (PDMS) microchannel (300 μm wide, 45 μm deep) using a confocal micro-PIV system. Applying this combination, measurements of trace particles seeded in the flow were performed for both fluids at a constant flow rate (Re = 0.02). Velocity profiles were acquired by successive measurements at different depth positions to obtain three-dimensional (3-D) information on the behavior of both fluid flows. Generally, the velocity profiles were found to be markedly blunt in the central region, mainly due to the low aspect ratio (h/w = 0.15) of the rectangular microchannel. Predictions using a theoretical model for the rectangular microchannel corresponded quite well with the experimental micro-PIV results for the PS fluid. However, for the in vitro blood with 20% hematocrit, small fluctuations were found in the velocity profiles. The present study clearly shows that confocal micro-PIV can be effectively integrated with a PDMS microchannel and used to obtain blood velocity profiles along the full depth of the microchannel because of its unique 3-D optical sectioning ability. Advantages and disadvantages of PDMS microchannels over glass capillaries are also discussed.